Development of the Japanese Version of the State Self-Compassion Scale (SSCS-J) - Miyagawa, Yuki; Tóth-Király, István; Knox, Marissa C.; Taniguchi, Junichi; Niiya, Yu (Frontiers in Psychology, 2022)
Neff et al. (2021) developed and validated the State Self-Compassion Scale (SSCS), which measures self-compassionate reactions toward a specific negative event. The current study is aimed at developing the Japanese version of the State Self-Compassion Scale (SSCS-J) and extending Neff et al.’s (2021) findings by showing measurement invariance across sexes and demonstrating the construct validity of this scale. Across two studies (n = 596 in Study 1, n = 474 in Study 2), the bifactor exploratory structural equation modeling representation of the SSCS-J showed excellent fit in which a single global factor (i.e., self-compassion) and most of the specific factors (six subscales) were well defined. Study 1 further provided evidence for the measurement invariance across sexes. The SSCS-J was related with higher trait self-compassion and lower fear of and negative beliefs about self-compassion. In Study 2, participants who were instructed to be self-compassionate reported higher scores in the SSCS-J relative to those in the control condition. These results attest to the replicability of the factor structure of the SSCS in Japan and provide further evidence for the construct validity of this scale.